Addition of beans four and Mukene (Rastrineobola argentea) powder improves the nutritional, sensory and functional properties of maize four for porridge - Tumuhimbise, Gaston Ampek; Tumwine, Gerald; Nabubuya, Agnes; Mutatina, Boniface; Rwebiita, Atucungwiire; Basaza, Robert (Springer International Publishing, 2025)
Malnutrition is a burden among young children in Uganda due to inadequate intake of the required nutrients. Inadequate nutrient intake is partly caused by the use of plant based foods to wean infants. The plant based foods are high in calories but limited in other essential nutrients such as proteins, vitamins and minerals. This study aimed to develop maize-based composite flour enriched with locally available legumes namely; beans and soybeans and Rastrineobola argentea powder. Two formulations of maize-based composite flours with beans, soybeans and Rastrineobola argentea were made with one containing roasted beans and the other with unroasted beans. Flour blends were produced by mixing 55:20:20:5 (Maize: beans: soybeans: Mukene ( Rastrineobola argentea ) powder, w/w) while 100% maize flour was used as the control. The proximate composition results were: moisture content (5.03 to 5.32%), crude protein (10.11 to 19.00%), carbohydrate (63.17 to 79.60%), crude fat (3.96 to 4.52%) and crude fiber (2.10 to 4.40%). Energy content was between 332 and 377 kcal/100 g. Mineral content were: Calcium (14.80 to 1869.12 mg/100 g), Iron (1.45 to 58.97 mg/100 g). Functional properties results obtained were: water absorption capacity (150.71 to 305.00%), oil absorption capacity (86.01 to 200.00%), bulk density (0.63 to 0.83 g/ml), swelling power (2.6 to 7.8%), and solubility (0.5 to 19.0%). The substitution of maize flour with beans, soybean and Rastrineobola argentea had significant reduction in the overall sensory acceptability of porridge. Addition of beans, soy and Rastrineobola argentea powder flour resulted into maize based composite flour with high peak (490.33 to 839.33 cP), trough viscosity (467.00 to 803.33cP), set back (1124.00 to 1721.33cP) and final viscosities (1591.00 to 2524.67cP). Peak time (5.93 min) and pasting temperature (86.40 to 89.867 °C) of the composite flour were lower than those of maize flour (peak time; 6.93 min, pasting temperature; 93.67 °C). It was concluded that the addition of beans, soybeans flour and Rastrineobola argentea powder to maize flour enhanced the nutritional and functional properties of the composite flours. Therefore, the developed composite flour can be used in the management of undernutrition in developing countries.